Análise teórica e experimental do desempenho de duto de luz, na cidade de São Carlos - Silva, Andrigo Demétrio da (Universidade Federal de São Carlos, 2006)
Illumination electric systems are responsible by expressive consumption of energy in buildings. Daylight, on the other hand, is abundant, free and more favorable to health and to the efficiency of people activities. However the side-windows system, when it is used alone, presents limitations in illuminance distribution. These limitations can be attenuated by usage of sunlight redirecting devices, such as Light Pipes (LPs). LPs collect daylight, conduct it by successive reflections and deliver it to an internal ambient, providing more visual comfort and saving energy. This research is carried out by studying the diffuser, the internal illumination and the collection, conduction and distribution of light by LP. To analyze the diffuser that would be used on the distribution of light, different materials were exposed to daylight and their behavior under the sunlight was evaluated. An appropriate diffuser was not found, therefore the milky acrylic was used as a diffuser panel. LP systems contribution in illumination was quantified and analyzed by monitoring scale models and the results were compared to conventional daylight systems. LP different sections (square and rectangular) with mirror internal surfaces were analyzed to evaluate their performances and they were compared to evaluate the influence of geometry, internal reflectance and LP orientation. Results indicate that the LP with square section is more efficient. Also sky conditions were analyzed and their influence in the internal illuminance. Experimental data were compared to a theoretical analysis. At last an evaluation of potential for energy savings by using LP was performed.
Keywords: Iluminação; Iluminação natural; Dutos de luz; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL